The study of the influence of technological parameters of the impulse process on the formation of the weld metal and the microstructure of the heat-affected zone - Maksymov, S. Yu.; Gavryliuk, A. A.; Shlapak, L. S. (JOURNAL OF HYDROCARBON POWER ENGINEERING, 2020)
With prolonged use of metal structures, the likelihood of their mechanical destruction increases. This is largely true of welded joints of pipelines. One of the promising ways to solve the issue of increasing their service life is the development of welding methods based on the use of pulse control of the energy parameters of the process. The pulsed welding mode allows for controlled heat input to the weld zone, control the melting mode of the electrode metal and the formation of the weld metal structure and the heat-affected zone (HAZ). Two types of metal transfer from the electrode to the weld pool were used in the work: with short circuits and without them, that is, welding was performed on a "long" arc. At a constant feed rate of the electrode wire, the welding mode was changed by changing the shape of the current-voltage characteristics of the power source. It is established that with increasing pulse-arc welding frequency, pulse-arc welding on the effect of influence on the HAZ metal approaches the process of welding by a stationary arc. The results of metallographic studies showed a slight decrease in the total width of the HAZ with an increase in frequency to 50 Hz. A similar trend is observed for the area of ​​coarse-grained in the HAZ. However comparedwith a stationary welding process, the width of this section decreases more significantly - by 25 ... 30%. Thus, in the case of welding pipe steels due to the application of technology with a pulsed process, there is a prospect of influencing the structure of the HAZ overheating aria at different frequencies and relatively small linear energies (6.0 ... 6.2 kJ / cm). From a practical point of view, this makes it possible to reduce the proportion of an unfavourable, non-plastic overheating zone in the HAZ, which is important for cases of repair of thinning of the pipe walls during the surfacing of defects in an existing pipeline in a mechanized manner.